Exposure Levels to Electromagnetic Fields of Wi-Fi Systems measured in the World and Latin America. A review - Cruz Ornetta, Víctor Manuel (2023)
Several studies have been conducted on the electromagnetic fields (EMF) of Wi-Fi systems from the point of view of health (possible effects) and engineering studies also (exposure levels) but there is a lack of research on this topic in Latin America. The aim of this study was to review studies worldwide and in Latin America on the levels of exposure to EMF from Wi-Fi systems. The methodology was based mainly on the systematic review of the database specialized in electromagnetic fields and health EMF-PORTAL; papers by Latin American authors were also included. The eligibility criteria for the papers to be included in the review were based on the PECO (Population, taking these criteria into account, there were finally 37 articles to be reviewed. As a result, two summary tables were formulated, observing that the Wi-Fi levels in all cases were less than 0.08% of the ICNIRP population exposure limits and that the EMF contribution of Wi-Fi systems with respect to the total exposure, in most cases it is very small (0.009% to 20.9% of overall exposure). It is concluded that it is necessary to carry out measurements that allow us to better characterize the exposure to these EMFs in Latin America and to carry out our own review of the health effects to avoid the misperception of Wi-Fi systems.